Design And Experimental Study Of A Solar System For Heating Water Utilizing A Linear Fresnel Reflector - Ghodbane, M.; Boumeddane, B.; Said, N. (University of Eloued جامعة الوادي, 2016)
This work presents a design and an experimental study of a linear Fresnel reflector solar with trapezoidal cavity. This prototype is used for heating the tap water. The reflector was designed, constructed and tested in mechanical engineering department, University of Blida 1, Algeria. Various combinations of reflecting mirrors were tried to achieve hot temperature at the concentration line. The absorber tube was made of copper; it was painted with black paint and covered by selective suitable surface. The quantity of heat available to the absorber tubes was evaluated and compared with 7, 9 and 11 mirrors. The experimental works on the concentrator were accomplished within two days in the winter of 2015. Water temperature reached a maximum of 74 °C with eleven reflective mirrors. The maximum value of the thermal efficiency is 29.21%. The results obtained are very encouraging for using linear Fresnel concentrator in the solar fields allocated to the domestics and industrial water-heaters.
Articale in Journal of fundamental and Applied Sciences Vol. 08, N. 03
Keywords: Solar energy; design, linear Fresnel reflector; thermal efficiency; solar water-heater.